2002
DOI: 10.1016/s0960-8524(02)00045-7
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium removal by living cells of the marine microalga Tetraselmis suecica

Abstract: Cadmium removal by living cells of the marine microalga Tetraselmis suecica was tested in cultures exposed to different cadmium concentrations (0.6, 3, 6, 15, 30 and 45 mg/l). The EC50 for growth was 7.9 mg Cd/l after six days of exposure. The cadmium removed was proportional to the concentration of this metal in the medium and it was dependent on the time of exposure; cultures with higher cadmium concentration removed a higher amount of this metal. In cultures exposed to 0.6 mg/l, T suecica cells removed 98.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
61
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(72 citation statements)
references
References 22 publications
9
61
1
1
Order By: Relevance
“…The more cadmium concentration in the medium, the more adsorbed-intracellular Cd difference increased (P<0.05), which means that much of the cadmium was removed by its uptake into the cell at all cadmium concentrations (≤10 mg L -1 ). This result is in accordance with Perez-Rama et al (2002) who found that the amounts of Cd taken up by intracellular were quite higher than those in adsorbed on the surface of Tetraselmis suecica cells.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The more cadmium concentration in the medium, the more adsorbed-intracellular Cd difference increased (P<0.05), which means that much of the cadmium was removed by its uptake into the cell at all cadmium concentrations (≤10 mg L -1 ). This result is in accordance with Perez-Rama et al (2002) who found that the amounts of Cd taken up by intracellular were quite higher than those in adsorbed on the surface of Tetraselmis suecica cells.…”
Section: Resultssupporting
confidence: 93%
“…However, the metal is not uptaken into cells by non-living biomass, since metals are adsorbed only on the algal surface (Fehrmann and Pohl, 1993). Previous studies (Matsunaga et al, 1999;Perez-Rama et al, 2002) and the present one using T. allenii indicate that intracellular Cd levels are higher than the bio adsorbed, which indicates that living biomass of T. allenii cells would be more effective for Cd removal than non-living biomass.…”
Section: Resultsmentioning
confidence: 47%
“…to 10 −5 M. Pérez-Rama et al (2002) also reported that intracellular metal levels in the marine microalga Tetraselmis suecica were higher than the bioadsorbed. Microalgae have several mechanisms which could protect themselves against metal toxicity.…”
Section: Discussionmentioning
confidence: 88%
“…Cell wall exclusion of metal ions (Andrade et al 2004;Macfie and Welbourn 2000;Pérez-Rama et al 2002) and intracellular detoxification (Gekeler et al 1988;Howe and Merchant 1992;Scarano and Morelli 2002;Surosz and Palinska 2004;Twiss and Nalewajko 1992) by binding to phytochelatins or polyphosphate had been demonstrated in a variety of algal species in response to elevated metal concentrations. The cell wall, composed mainly by carbohydrates and proteins, is the first barrier in the uptake of the metals (Pérez-Rama et al 2002) and has the capacity to bind metal ions in negatively charged sites (Macfie and Welbourn 2000). Andrade et al (2004) demonstrated that the acidic polysaccharides of the cell walls of brown algae Padina gymnospora acted as metal binder for the nucleation and precipitation of metals when the algae were exposed to the environment contaminated by heavy metals.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution and uptake of metals was evaluated according to the modified method described by Perez-Rama and Alonso [13]. The cultures were harvested by centrifugation (13,000 g, 10 min) at the end of the experiments.…”
Section: Distribution and Uptake Of Metals In Pseudomonas Sp Mbr Aftmentioning
confidence: 99%